Impacto da incontinência urinária na função sexual feminina - Lucena, Suellen Viana (2017)
Introduction: Urinary incontinence (UI) is defined as the involuntary loss of urine that can affect sexual performance. Objective: to evaluate the impact of UI on female sexual function. Method: This is a mixed study. The research was developed in an urogynecology outpatient clinic of the Maternidade Escola Assis Chateaubriand (MEAC) and a private clinic Pelvic Clinic in Fortaleza. Data collection took place from September 2016 to July 2017, through individual interviews. The instruments applied were: the identification form used in the ambulatory of uroginecologia of the MEAC; the Brazilian Economic Classification Criterion (CCEB), proposed by the Brazilian Association of Research Companies (ABEP); International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) that assesses the impact of UI on quality of life and qualifies urinary loss; The Female Sexual Function Index (FSFI) that assesses the sexual function of sexually active women and a semi-structured individual interview script based on The Pelvic Organ Prolapse / Urinary Incontinence Questionnaire- IUGA revised (PISQ-IR) to assess sexual satisfaction. Quantitative data were analyzed using the Statistical Package for the Social Sciences (SPSS Inc., Chicago, USA) version 20.0 and qualitative data were evaluated using Bardin content analysis and IRAMUTEQ (R pour les Analyses Multidimensionnelles de Textes et de Questionnaires). The study was approved by the ethics committee of MEAC under number 1.739.920. Results: The sample consisted of 88 women with UI of stress or mixed, age ranged from 30 to 79 years, 45.4% had low level of schooling, 69.3% were married or lived in a stable union. As for CCEB, class C (38.6%) was the most predominant, followed by class DE (27.3%), class B (26.1%) and class A (8%). About 68% of the participants are attended at a public health institution. The negative UI interference in sexual life is associated with mixed UI (p = 0.01), loss of urine during penetration (p <0.01), vaginal looseness (p = 0.03), UI interference in life (p = 0.03), higher UI severity, and worse ICIQ-SF score (p = 0.01). Conclusion: Subtypes, UI severity, vaginal laxity, and sexual dysfunction are associated with the sexual subcategories of the PISQ-IR based script for women with UI, corroborating for a negative UI interference in women's sexual life. Those suggests the need for strategies to promote the sexual health of women with UI. Keywords: Urinary incontinence. Sexuality. Women.